Peningkatan Minat Belajar Dan Hasil Belajar Melalui Strategi Example Non Example Pada Mata Pelajaran Bahasa Inggris Siswa Kelas 3 Sd Negeri 01 Paseban Tahun Ajaran 2014/2015 - SUBEKTI, SRI (2016)
This study aims to increase interest in learning and learning outcomes through strategies example non-example on the subjects of English language students Grade 3 Elementary School 01 Paseban. This research is a classroom action research conducted in two cycles each cycle consisting of two meetings. Subject of research is the class teacher and the students of Class 3 SD Negeri 01 Paseban totaling 16 students. Methods of data collection using interviews, observation, documentation and testing. Data analysis technique used was qualitative descriptive data analysis through the stages of data reduction, data presentation, and data verification or conclusion. The results showed an increased interest in learning which include: 1) Caution before action 51.56% of students who pay attention, cycle I meeting 1 59.38% of the students, the first cycle of meetings 2 70.3% of students, the second cycle meeting 175% of students , the second cycle meeting 2 87.5% of students, 2) concentration in the act of 40.62% of students who concentrate, cycle I meeting 1 53.13% of the students, the first cycle of meetings 2 54.69% students, 59 second cycle meeting1, 68% of students, the second cycle meeting 2 73.43%, 3) 42.19% Enthusiastic before the action of enthusiastic students, cycle I meeting 1 53.13% of the students, the first cycle of meetings 2 64.06% of the students, the second cycle meetings 1 65.63% of the students, the second cycle 71.87% of students meeting 2, 4) Activeness before action 40.63% of the students, the first cycle meeting 154.69% of the students, the first cycle of meetings 2 59.38% of the students, the second cycle meeting 1 62.5% of students, the second cycle meeting 2 73.43% of the students. The average student learning outcomes also increased at an average pre-cycle student learning outcomes is 55 students that reached the pass standard many as three students (18.75%), in the first cycle increased to 62.2 1 meeting with students the pass standard valued at as much as 6 students (37.5%), the first cycle increased to 70.94 2 meeting with students whose value striking the pass standard 13 students (81.25%), the second cycle 1 meeting increased to 75 with all students have reached the pass standard and at the second meeting of the second cycle increased to 81.25 with a value of more than the pass standard all students. The conclusion of this study is that the use of example non example strategy can improve the interest in learning and learning outcomes in subjects of English language students Grade 3 Elementary School 01 Paseban the academic year 2014/2015.